Suppressive Effects of GSS on Lipopolysaccharide-Induced Endothelial Cell Injury and ALI via TNF-α and IL-6 - Lei Yi; Zengding Zhou; Yijuan Zheng; Mengling Chang; Xiaoqin Huang; Feng Guo; Quanming Zhao; Jingning Huan (Mediators of Inflammation)
Background. Under septic conditions, LPS induced lung vascular endothelial cell (EC) injury, and the release of inflammatory mediator launches and aggravates acute lung injury (ALI). There are no effective therapeutic options for ALI. Genistein-3′-sodium sulfonate (GSS) is a derivative of native soy isoflavone, which exhibits neuroprotective effects via its antiapoptosis property. However, whether GSS protect against sepsis-induced EC injury and release of inflammatory mediators has not been determined. In this study, we found that GSS not only downregulated the levels of TNF-α and IL-6 in the lung and serum of mice in vivo but also inhibited the expression and secretion of TNF-α and IL-6 in ECs. Importantly, we also found that GSS blocked LPS-induced TNF-α and IL-6 expression in ECs via the Myd88/NF-κB signaling pathway. Taken together, our results demonstrated that GSS might be a promising candidate for sepsis-induced ALI via its regulating effects on inflammatory response in lung ECs.